The New Reference Points for Modernizing Vocational Education Given the Informational Boom - G. F. Shafranov-Kutsev (Образование и наука)
The article analyzes the peculiarities and scales of the modern informational outburst, its implications in industrial and vocational training spheres. Simultaneously, along with the growing accumulation of the information data, a considerable part of the recently stored knowledge becomes obsolete. It results in shortening a half-decay period of specialist’s competence and, therefore, requires the cardinal updating of the vocational training system. The logic of information society development brings forth the need for the compulsory higher education and various new forms of further training. Fast growing number of telecommunication facilities and information technologies make it possible to establish the unified chain of vocational training institutions over the Internet and transform the methodology approaches to organization and content of the vocational education. Their libraries tend to turn into powerful informational library centers with fundamentally new functions. The author makes the conclusion that the growing level of people’s education is the fast way to social progress and the life standards rising.